THE EFFECTIVENESS, IMMUNOGENICITY, AND SAFETY OF THE Escherichia coli BASED BIVALENT HUMAN PAPILLOMAVIRUS (TYPES 16 AND 18) VACCINE PREVENTING CERVICAL CANCER: A Systematic Review - Masykur, Umar Jundullah; Janet, Karensa Abby (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Cervical cancer is the fourth most prevalent cancer worldwide and ranks second in Indonesia, with a high mortality rate among women. Cervical cancer ranks highest in treatment costs in Indonesia. HPV-16/18 infection causes nearly all cases of cervical cancer. The HPV-16/18 bivalent vaccine made with E. coli holds potential as a more affordable HPV vaccine than other commercial vaccines. Objective: This systematic review aimed to discuss the effectiveness, immunogenicity, and safety of the bivalent HPV-16/18 vaccine produced by E. coli based on evidence from available studies. Methods: This systematic review included valid experimental studies retrieved from PubMed, Cochrane, ScienceDirect, and Taylor and Francais databases that met the inclusion criteria. The search method used Boolean operators, with the literature cited from 2014 to 2024. Results and Discussion: Seven studies met the inclusion criteria. The results of all studies indicate that the bivalent HPV-16/18 vaccine produced by E. coli has a high effectiveness and good immunogenicity. There were no significant side effects associated with vaccination, and most of the side effects were minor. Conclusion: The bivalent HPV-16/18 vaccine produced by E. coli could serve as a reliable and economical alternative to prophylactic HPV vaccination for cervical cancer prevention.